2021
DOI: 10.1101/2021.07.19.452809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR screens for host factors critical for infection by SARS-CoV-2 variants of concern identify GATA6 as a central modulator of ACE2

Abstract: The global spread of SARS-CoV-2 lead to the most challenging pandemic in this century, posing major economic and health challenges worldwide. Revealing host genes essential for infection by multiple variants of SASR-CoV-2 can provide insights into the virus pathogenesis, and facilitates the development of novel broad-spectrum host-directed therapeutics. Here, employing genome-scale CRISPR screens, we provide a comprehensive data-set of cellular factors that are exploited by WT-SARS-CoV-2 as well as two additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 94 publications
(118 reference statements)
2
2
0
Order By: Relevance
“…Both screens identified ACE2 as the top-ranked gene as expected, along with other known spike-binding receptors including CLEC4M in the arrayed screen (Fig 1C and S2 Data) and the transcription factor GATA6 in the CRISPR activation screen [20] (Fig 1D and S3 Data). The CRISPR activation (CRISPRa) screen was able to detect even weak spike binding signals, identifying the transcription factor EBF1 despite causing only a small increase in ACE2 levels (S2 Fig and S1 Table and S4 Data).…”
Section: Systematic Screening For Sars-cov-2 Spike Binding Interactio...supporting
confidence: 59%
“…Both screens identified ACE2 as the top-ranked gene as expected, along with other known spike-binding receptors including CLEC4M in the arrayed screen (Fig 1C and S2 Data) and the transcription factor GATA6 in the CRISPR activation screen [20] (Fig 1D and S3 Data). The CRISPR activation (CRISPRa) screen was able to detect even weak spike binding signals, identifying the transcription factor EBF1 despite causing only a small increase in ACE2 levels (S2 Fig and S1 Table and S4 Data).…”
Section: Systematic Screening For Sars-cov-2 Spike Binding Interactio...supporting
confidence: 59%
“…Both screens identified ACE2 as the top-ranked gene as expected, along with other known spikebinding receptors including CLEC4M in the arrayed screen (Figure 1C) and the transcription factor GATA6 in the CRISPR activation screen (Israeli et al, 2021) (Figure 1D). The CRISPRa screen was able to detect even weak spike binding signals, identifying the transcription factor EBF1 despite causing only a small increase in ACE2 levels (Supplemental Figure 2, Supplementary Table 1).…”
Section: Systematic Screening For Sars-cov-2 Spike Binding Interactions Identifies Lrrc15supporting
confidence: 56%
“…Several studies have shown ACE2 transcription in human cells is regulated by multiple factors ( 31 33 ). Wei et al.…”
Section: Discussionmentioning
confidence: 99%
“…found that bromodomain-containing protein 2 (BRD2), a transcriptional regulator, promotes ACE2 transcription, and the authors further demonstrated that the BRD2 inhibitor ABBV-774 inhibited SARS-CoV-2 infection in vitro and in vivo ( 32 ). The transcriptional regulator GATA-binding protein 6 (GATA6) was shown to affect the susceptibility of Calu-3 cells to SARS-CoV-2 infection by directly binding to the ACE2 promoter ( 33 ). Thus, multiple host factors have been implicated in regulating cellular susceptibility to SARS-CoV-2 infection through modulation of ACE2 transcription.…”
Section: Discussionmentioning
confidence: 99%